The position of the Kurds from the Islamic state until the end of the Umayyad era - Maya, Ass. Prof. Dr. Marwan Attia (Thi Qar Arts Journal, 2023)
The subject of the study in Kurdish nationalism is an important topic because it is characterized by showing the bonds of the spectra of Islamic peoples and the extent of the historical depth that Kurdish nationalism occupies in the body of the Islamic state.   The most important areas in which the Kurdish tribes existed, whether they were mountainous or plain, and the first beginnings of the collision of Muslims with the Kurds during the Islamic incursion into the body of the Sasanian Empire, as well as shedding light on the conditions of the Kurds in early Islam and showing their opposition to the central government during the caliphate of Imam Ali (p), As they organized the movements of the Kharijites, whose basis they became later, then we stopped at dealing with the position of the Kurds during the Umayyad government, and their positions were oscillating between opponents of the central state and between supporters of it. It made Shahrzor its headquarters, and it is one of the most important strongholds of the Kurds. After that, we found the Kurds unorganized for the opposition movement that was carried out by Al-Mukhtar Al-Thaqafi due to the different ideological orientations. One of the fiercest opponents of the Umayyad authority under the banner of the Kharijites in the regions of the Euphrates island and Mosul